Can films impact on visitation to film locations? - Quintal, Vanessa; Roff, Elizabeth (Detay Anatolia Akademik Yayincilik Danismanlik Org. Turz. Ltd, 2012)
While research acknowledges the impact films have on viewers’ destination choices, an empirically tested decision-making framework is required that explains film viewers’ intention to visit a place. The sample comprised 230 film viewers at an Australian cinema. Empathy had a positive effect on place familiarity. Perceived performance/ financial risk produced a negative effect on place familiarity. Place familiarity had a positive effect on place image, which in turn, produced positive effect on attitudetoward visiting the place. Finally, attitude toward visiting the place had a positive effect on intention to visit the place. Such a framework is relevant to the tourism and entertainment sectors. It provides theoretical underpinning for future empirical studies and helps film makers and destination managers in delivering consistent messages about a film and its location.